ANALISIS PENYUSUNAN ANGGARAN KOMPREHENSIF PADA USAHA JASA LAUNDRY KILOAN : STUDI KASUS PADA KING CLEAN LAUNDROMAT - Aisyah, Nur; Siregar , Yulianti; Tafrijah , Murni; Vientiany, Dini (CV. Barokah Publsiher, 2025)
The preparation of a comprehensive budget is an important aspect of financial management in service businesses, including kilogram-based laundry services. A comprehensive budget functions as a tool for planning, controlling, and managerial decision-making to ensure that operational activities run effectively and efficiently. This study aims to analyze the process of preparing a comprehensive budget in a kilogram-based laundry service business through a case study of KING CLEAN LAUNDROMAT. The research uses a qualitative approach with data collection techniques consisting of interviews, observations, and documentation. The results show that KING CLEAN LAUNDROMAT has prepared several budget components, such as revenue budgets and operational cost budgets; however, the comprehensive budgeting process has not yet been conducted in a systematic and integrated manner. Limited managerial knowledge and the absence of written financial planning are identified as the main obstacles in preparing a comprehensive budget. This study is expected to provide insights and recommendations for laundry service business owners in developing a more structured comprehensive budgeting system to improve business performance and sustainability.